Investigating the effect of Antecedent Rainfall on Pore-Water Pressure Distribution Characteristics in Residual Soil Slopes under Tropical Rainfall - Mohamed Elbyhagi Elfadil (Challenging Issues on Environment and Earth Science Vol. 8, 2021)
The major criteria associated with unsaturated soil slope instability are characteristics of variations in pore-water pressure distribution. They are directly influenced by flux boundary conditions at the soil–atmosphere interface (rainfall infiltration, evaporation, and evapo-transpiration). Using Jet Fill Tensiometer, two slopes were instrumented at Universiti Teknologi Malaysia’s Skudai campus in Malaysia. The field monitoring data was examined to quantify pore-water pressure distributions in residual soil slopes under tropical climate conditions in order to investigate the effect of antecedent rainfall on pore-water pressure distributions. Slope stability analyses were also carried out for each slope at a depth of 1.0-2.0 metre to define the factor of safety range. The results showed that antecedent rainfall, initial pore-water pressures prior to a significant rainfall event, and the magnitude of the rainfall event all play a significant role in the development of the worst pore-water pressure condition on a slope. In residual soils with low permeability, the influence of antecedent rainfall in the establishment of the worst pore-water pressure state was found to be more significant than in residual soils with high permeability.The factor of safety of low permeability residual soils was found to be unaffected by the worst pore-water pressure condition.